Reference Test Maps for Path Planning Algorithm Test - Kim, Jingyu; Woo, Sang Hyo (Arman) (International journal of control, automation, and systems, 2018)
Path planning is an essential task for commercialize autonomous robots and vehicles. There are various path planning algorithms but most of the algorithms do not compare with same map. If there is reference test maps, it will be useful for various path planning algorithms comparison. In this paper, 2D/3D reference test maps are proposed for path planning and the maps are tested by famous path planning algorithms.